Revisiting qualitative methods in social science research - Aleaz,Bonita,Ed; Partha Pratim Basu,Ed (Orient Blackswan, 2010)
Across the world, There has been a surge of interest in the methodological tools used in qualitative research in the social sciences. This is particularly so in the developing world, where academic research continues to be guided by research methods developed in a Euro-American context. In India, especially, recent political, social and ideological upheavals have led to new ways of understanding states and society. Have the horizons of knowledge creation expanded? What are the new texts that have emerged and how many find place in classrooms? How useful are they in the context of the developing world. Revisiting qualitative methods in social Science research highlights a variety of qualitative methods of researched as gathering data from folk songs and conducting focus group discussions with village women—that have emerged in India. Such methods, The authors argue, make visible hitherto unseen issues and give voice to the voiceless imperative in contexts such as ours. The book also highlights the methods used to research specific areas such as caste, one of the distinctive features of this volume. The chapters detail novel methods such as Unobtrusive research, mobile methods and contingent behaviour and where these can be used, citing examples not only from India, but also from other countries like Malaysia and Botswana.